Revisiting percutaneous balloon mitral valvotomy technique and safety in various population: an evidence-based case report and literature review - Habib, Faisal; Mendel, Brian; Fauzan, Rivhan; Nasution, Ali Nafiah (Frontiers in Cardiovascular Medicine, 2024)
Percutaneous balloon mitral valvotomy (PBMV) is a good and preferred therapy choice over surgical commissurotomy for patients with rheumatic mitral stenosis (MS). However, interventional cardiologists must recognize that treating patients with rheumatic MS poses unique challenges for each patient, especially in special populations such as pregnant patients or patients with arrhythmias like atrial fibrillation (AF), which can complicate procedures. Based on information from observational studies, PBMV may be a safe and efficient treatment for improving outcomes in MS women who do not have substantial subvalve illness in a specific demographic. A successful PBMV helps to tolerate hemodynamic changes during pregnancy and dramatically reduces mortality. However, there is a paucity of studies on women with poor valve morphology who are not contraindicated, and it has to be seen if PBMV is used in these situations during pregnancy. Conversely, AF leads to a lower PBMV success rate as well as worse long-term and in-hospital outcomes.